Kemampuan komunikasi matematis siswa SMP PGRI Cibeureum menggunakan model problem based learning pada materi penyajian data - Nurliah, Eneng; Sabandar, Jozua; Bernard, Martin (IKIP Siliwangi, 2025)
This research aims to examine the improvement of mathematical communication skills of junior high school students in grade VII using the Problem Based Learning (PBL) model. The method used is quantitative with a quasi-experimental design involving two sample groups. One group is called the experimental class because it receives learning with the Problem Based Learning (PBL) model, the other is the control class whose learning uses the conventional model. The first meeting was given a pre-test and the last meeting was given a post-test. The population in this study was all grade VII of SMP PGRI Cibeureum. Then 2 classes were determined as samples, namely class VII-A as the experimental class and class VII-C as the control class. The data collection technique in this study used an instrument of students' mathematical communication skills which was given twice, namely during the Pre-test and Post-test. Data processing and analysis using Microsoft Excel application and SPSS software ver 25.0, the results of this research analysis show that the increase in mathematical communication skills of students of SMP PGRI Cibeureum whose learning uses the Problem Based Learning (PBL) Model is better than those who use conventional learning.